Analisis Motivasi Pengunjung Museum Macan Jakarta - Fitriana, Rina; Rahmitasari, Nurima; Yoseli, Marcelina (Jurnal Ilmiah Pariwisata, 2020)
MACAN Museum (Museum of Modern and Contemporary Art in Nusantara) has a wide collection of modern and contemporary Indonesian arts up to the first international scale in Indonesia, and is one of the tourist attractions in Jakarta that is preferred by various circles. The collection is packaged with the concept of art shows and exhibitions that can be enjoyed by every visitor. This research aims to analyze the motivation of visitors coming to the museum using quantitative descriptive methods. Unit of analysis is the visitors of MACAN museum, meanwhile the independent variable is the visitors’ motivation. Data was taken by giving questionnaire to 100 respondents, having observation, and doing structured interviews. The data were analyzed by excel and presented in the frequency table and pie chart. The results showed that of the four motivations, cultural motivation obtained the highest value as the most motivating factor for visitors with a value of 4.19, and the average total value of the four motivations is 3.84 which states that visitors are motivated to visit the MACAN museum. Keywords: MACAN Museum, Visitor Motivation, MICE, Contemporary Art